2021
DOI: 10.1017/jfm.2021.506
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced breaking of internal gravity waves

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…We anticipate that this reasoning will apply to more general overturning structures in the ocean. Indeed, Howland et al (2021) find a similar competition between shear and convective instabilities in the interaction between a large-scale breaking gravity wave and a background sinusoidal shear flow.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We anticipate that this reasoning will apply to more general overturning structures in the ocean. Indeed, Howland et al (2021) find a similar competition between shear and convective instabilities in the interaction between a large-scale breaking gravity wave and a background sinusoidal shear flow.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, Howland et al. (2021) find a similar competition between shear and convective instabilities in the interaction between a large-scale breaking gravity wave and a background sinusoidal shear flow.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Field studies have shown that there is considerable spatial variation in the mixing, typically being weaker in the ocean interior and more intense near the ocean floor and boundaries (Polzin et al 1997;Waterhouse et al 2014). The process of mixing involves a combination of internal wave breaking and shear-driven mixing (Winters et al 1995;Howland, Taylor & Caulfield 2021;Mashayek, Caulfield & Alford 2021), as well as localised boundary mixing (Thorpe 2007;Echeverri et al 2009;Winters 2015;Jagannathan, Winters & Armi 2017;Polzin & McDougall 2022) which then interacts with the remainder of the fluid. From a theoretical perspective, turbulent mixing in a stratified fluid involves a number of complex processes, and depends in detail on the balance between the dissipation of kinetic energy, the generation of potential energy, the ambient stratification and both the mean velocity and the shear (Osborn 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The process of mixing involves a combination of internal wave breaking and shear-driven mixing (Winters et al. 1995; Caulfield 2021; Howland, Taylor & Caulfield 2021; Mashayek, Caulfield & Alford 2021), as well as localised boundary mixing (Thorpe 2007; Echeverri et al. 2009; Winters 2015; Jagannathan, Winters & Armi 2017; Polzin & McDougall 2022) which then interacts with the remainder of the fluid.…”
Section: Introductionmentioning
confidence: 99%